Antibacterial Activity Test of Red Ginger Extract (Zingiber officinale var. Rubrum) Against Streptococcus pyogenes In vitro - Samira Assegaf; Arthur Pohan Kawilarang; Retno Handajani (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2020)
Introduction: Red ginger (Zingiber officinale var. rubrum) is known as an antibacterial agent. Streptococcus pyogenes is the most common bacterial cause of pharyngitis in children and adults. Over the years, antibiotic resistance case is increasing. Therefore, further research of other substances to find an bactericidal or bacteriostatic agent is needed. The aim of this study is to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of Z. officinale var. rubrum against S. pyogenes. Methods: Serial dilution test of red ginger extract in Mueller hinton broth (8 concentrations of red ginger extract : 80%, 40%, 20%, 10%, 5%, 2,5%, 1,25%, and 0,625%) and positive control (1 ml bacterial suspension in Mueller hinton broth) was used to determine MIC. MBC was determined by culturing solutions from the previous dilution test into blood agar plate.lResults: MIC of red ginger extract against S. pyogenes could not be determined because the color of red ginger extract affected the turbidity of the dilution test result. MBC of red ginger extract against S. pyogenes was at concentration 20% of red ginger extract.Conclusion: Z. officinale var. rubrum showed antibacterial activity against S. pyogenes.